1)cos^2(альфа)-cos^4(альфа)+sin^4(альфа)
2)1-2cos^2(бета)
------------------------
cos(бета)+sin(бета)
3) (sin^2альфа+tg^2альфа sin^2 альфа) Ctg(альфа)
4) cos^2(альфа)-1
-------------------------- + tg^2(альфа)
cos^4 (альфа)

2

Ответы и объяснения

2013-02-17T20:07:08+04:00

знаю только первое,остальное без понятия

2013-02-17T20:52:01+04:00

3)(sin^2a+sin^4a/cos^2a)*cosa/sina=sin^2a(cos^2a+sin^2a)*cosa/(sina*cos^2a)=(sina/cosa)

4)(cosa-1)(cosa+1)/cos^4a+sin^2a/cos^2a=(cos^2a-1+sin^2a*cos^2a)/cos^4a=(sin^2a*cos^2a-sin^2a)/cos^4a=sin^2a(cos^2a-1)/cos^4a=tg^2a(cos^2a-1)/cos^2a